2004
DOI: 10.1191/1362168804lr134oa
|View full text |Cite
|
Sign up to set email alerts
|

Learner proficiency and focus on form during collaborative dialogue

Abstract: One of the challenges in content-based instruction in second language classrooms is how to focus on form in a way that is both effective and appropriate. The use of collaborative tasks that push learners to consciously reflect on their own language use (i.e., produce ‘language-related episodes’) while conveying meaning has been proposed as one way to accomplish this goal. Studies investigating the use of collaborative tasks that encourage learners to produce language-related episodes (LREs) have been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
308
12
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(394 citation statements)
references
References 20 publications
45
308
12
1
Order By: Relevance
“…The study also found that learners fro m h igher proficiency levels may be more likely to have more metatalk and to reach more correct resolutions to their linguistic problems during collaborative engagements compared to their less proficient counterparts. Leeser (2004) similarly investigated the effect of proficiency on the occurrence and the outcome of the LREs in an EFL context (i.e., Spain). Ten L2 learners were assigned into five dyads; two of the dyads included pairs of h ig h proficiency (two high-high); t wo of the dyads included pairs of low p roficiency (two low -lo w).…”
mentioning
confidence: 99%
“…The study also found that learners fro m h igher proficiency levels may be more likely to have more metatalk and to reach more correct resolutions to their linguistic problems during collaborative engagements compared to their less proficient counterparts. Leeser (2004) similarly investigated the effect of proficiency on the occurrence and the outcome of the LREs in an EFL context (i.e., Spain). Ten L2 learners were assigned into five dyads; two of the dyads included pairs of h ig h proficiency (two high-high); t wo of the dyads included pairs of low p roficiency (two low -lo w).…”
mentioning
confidence: 99%
“…In addition, LREs were also coded the outcome of the talk as correct/acceptable, incorrect/unacceptable, or unresolved (Leeser, 2004 …”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Leeser (2004) investigated how the different proficiency had an impact on learner proficiency towards the production of LREs (Storch, 2007). This study revealed that higher proficient learners were able to produce more LREs compared to their lower counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is noteworthy that although students may usually be paired with classmates of similar or different proficiency levels in a L2 writing class, the research investigating the impact of proficiency-pairing in L2 writing remains scant, and most of the research on peer dyads in either L2 writing or language learning in general mainly focused on the process of peer interactions, with little attention paid to the effects of those interactions on students' subsequent draft revisions (e.g., Leeser, 2004;Lockhart & Ng, 1995;Nelson & Murphy, 1993;Storch, 1998Storch, , 2002aStorch, , 2002bStorch, , 2005aStorch, , 2005bStorch, , 2007aStorch, , 2007bStorch & Aldosari, 2013;Watanabe, 2008;Watanabe & Swain, 2007). Earlier studies like Lockhart and Ng (1995), Nelson and Murphy (1993), and Storch (2002a) examined the types of student interactions that were likely to result in students' incorporation of a higher percentage of peer response into their draft revisions.…”
Section: Literature Reviewmentioning
confidence: 99%